The development of integrated framework for electronic records management in Sarawak state goverment / Arpah Adenan - Adenan, Arpah (2018)
The effective implementation of records management is largely dependent on the policy, legislation, standards, codes of best practice, guidelines and manuals, training, services and support. However, many existing models lack the integration of these elements particularly in the implementation of electronic records management (ERM). Hence, this study aims to develop an integrated organizational framework on ERM for the Sarawak State Government through three (operational objectives: (a) to examine ERM practices in the Sarawak State Government within the context of best practice organizational framework; (b) to propose new modified organizational framework elements suitable to the findings of the study; and (c) to identify the role and responsibility for ERM within the organizational framework. To address these objectives, the research adopted a case study approach with qualitative data gathered from the literature review and face-to-face interviews. Qualitative data was gathered from five informants from five purposive samples of Sarawak State Government agencies. The study has identified a generic organizational framework model for records management with its conceptual underpinning elements from the literature. The elements of the generic organizational framework model were used to explore electronic records management practice in the selected Sarawak State Government. Ultimately, the findings revealed that the six elements of the generic organizational framework model matched the situation of the Sarawak cases, but with extra 24 new elements, local to the Sarawak context were identified as strong drivers to be integrated into the six main elements of the generic organizational framework. As a result, a new modified integration framework was developed for the implementation of electronic records management in the Sarawak State Government. In order to assess the extent of its universal application, similar projects employing the same methods but conducted in contrasting environments such as the Malaysian Federal Government or other Malaysian State Governments or in other countries would be of great value.